2016
DOI: 10.1186/s12885-016-2200-x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopamine tartrate, an inhibitor of Hedgehog signaling, strongly interferes with mitochondrial function and suppresses aerobic respiration in lung cancer cells

Abstract: BackgroundAberrant Hedgehog (Hh) signaling is associated with the development of many cancers including prostate cancer, gastrointestinal cancer, lung cancer, pancreatic cancer, ovarian cancer, and basal cell carcinoma. The Hh signaling pathway has been one of the most intensely investigated targets for cancer therapy, and a number of compounds inhibiting Hh signaling are being tested clinically for treating many cancers. Lung cancer causes more deaths than the next three most common cancers (colon, breast, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 47 publications
(51 reference statements)
4
32
0
Order By: Relevance
“…Supporting this concept, Alam et al (2016a) demonstrated that enhanced mitochondrial aerobic respiration is necessary for many types of cancer cells to gain tumorigenic and drug-resistant potential, such as non-small cell lung cancer (NSCLC) and breast cancer. Inhibition of mitochondrial respiration by Hedgehog inhibitors, such as cyclopamine tartrate, could strongly interfere with cell proliferation and induce apoptosis in NSCLC (Alam et al, 2016b). In addition, studies have demonstrated that based on the context, the mitochondrial mass can serve as either a pro-survival or pro-death modulator in tumor development and progression (Joshi et al, 2016).…”
Section: Mitochondrion As a Target Of Tigmentioning
confidence: 99%
“…Supporting this concept, Alam et al (2016a) demonstrated that enhanced mitochondrial aerobic respiration is necessary for many types of cancer cells to gain tumorigenic and drug-resistant potential, such as non-small cell lung cancer (NSCLC) and breast cancer. Inhibition of mitochondrial respiration by Hedgehog inhibitors, such as cyclopamine tartrate, could strongly interfere with cell proliferation and induce apoptosis in NSCLC (Alam et al, 2016b). In addition, studies have demonstrated that based on the context, the mitochondrial mass can serve as either a pro-survival or pro-death modulator in tumor development and progression (Joshi et al, 2016).…”
Section: Mitochondrion As a Target Of Tigmentioning
confidence: 99%
“…Cyclopamine, the inhibitor for Smo, has shown anti-cancer activity [17]. In this study, we found that over-expression of WW45 promoted the ubiquitination and degradation of Gli1.…”
Section: Discussionmentioning
confidence: 56%
“…Cyclopamine tartrate inhibits SMO, thereby inhibiting Hedgehog signaling. In NSCLC HCC4017 cells, studies have demonstrated intensified oxygen consumption compared to benign HBEC cells from the same patient [20]. Low levels of glucose also contribute to higher oxygen consumption rates, and low levels of glutamine lower oxygen consumption rates.…”
Section: Lung Cancer Cells Are Extremely Susceptible To Inhibitors Ofmentioning
confidence: 99%
“…Consequently, when the mitochondria of tumor cells are tampered with to inhibit oxidative phosphorylation, these tumor cells become significantly more susceptible to cytotoxic drugs [16,19]. Agents such as cyclopamine tartrate, a water-soluble derivative of a molecule found in corn lilies [20]; metformin, an antidiabetic drug [18]; BAY 87-2243, a lead structure [15]; and microRNA-126, a microRNA [21] have shown potential to interfere with normal mitochondrial function in cancer cells. These molecules interact with various aspects of mitochondrial function, such as interfering with Hedgehog signaling and inhibiting Complex I. Cyclopamine tartrate functions by inhibiting Hedgehog signaling [20].…”
Section: Lung Cancer Cells Are Extremely Susceptible To Inhibitors Ofmentioning
confidence: 99%